Effect of sinusoidal magnetic field on a rough porous hyperbolic slider bearing with ferrofluid lubrication and slip velocity. (2nd July 2016) - Barik, M.; Mishra, S. R.; Dash, G. C.
Abstract : The main purpose of the present study is to analyse the effect of sinusoidal magnetic field on a rough porous hyperbolic slider bearing system. The analysis is subjected to (i) Beavers and Joseph's slip model measuring the effect of slip velocity (ii) Christensen and Tonder's stochastic model representing the transverse surface roughness (iii) Sinusoidal magnetic field as suggested by Patel and Deheri. The novelty of the present study lies with the effect of sinusoidal magnetic field strength combined with the stochastic roughness of the bearing surface on pressure distribution and load-carrying capacity. The striking result reported in the present study is that the sinusoidal magnetic field enhances the load-bearing capacity by a factor which amounts to 38.3% of increase in the load-carrying capacity. The magnetisation of the ferrofluid lubricant and slip parameter augment the load-bearing capacity within certain range.